Synthesis and Optimization of Cr (VI) Removal from Aqueous Solution by Activated Carbon with Magnetic Fe3O4Nanoparticles by Response Surface Methodology - L. Natrayan; R. Rajalakshmi; K. Amandeep Singh; Pravin P. Patil; Dhinakaran Veeman; Prabhu Paramasivam (Adsorption Science & Technology)
In this study, the activated carbon with Fe3O4 nanoparticles was synthesized and employed as an effective tool to remove the Cr (VI) from the aqueous solution. The process inputs like concentration of Cr (VI), the dosage of Fe3O4 nanoparticles in activated carbon, and pH of the aqueous solution were optimized by response surface methodology, and their effects were studied. The statistical analysis by ANOVA showed that the process inputs were significantly affected the removal rate, with the maximum impact provided by the pH of the aqueous solution. The best parameters were identified to be pH of 3, aqueous solution concentration of 12 mg/L, the dosage of 1.5 g/L, and adsorption time of 40 min. SEM, EDS, and FTIR characterized the synthesized activated carbon/Fe3O4 samples with magnetic characteristics. Adsorption isotherms and adsorption kinetics analyzed the chemical stability of the synthesized nanocomposite.